2005
DOI: 10.1039/b412294a
|View full text |Cite
|
Sign up to set email alerts
|

Conformational analysis of oleandomycin and its 8-methylene-9-oxime derivative by NMR and molecular modelling

Abstract: Conformations of the 14-membered macrolide antibiotic oleandomycin and its 8-methylene-9-oxime derivative were determined in various solvents. The experimental NMR data--coupling constants and NOE contacts--were compared with the results of molecular modelling--molecular mechanics calculations and molecular dynamics simulations. The conformational changes, on the right-hand side of the 14-membered ring, affected mostly the 3JH2,H3 values and NOE crosspeaks H3 or H4 to H11. Oleandomycin was found to be present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 24 publications
(40 reference statements)
3
29
0
Order By: Relevance
“…Their results [146][147][148][149][150], and those of other groups [151][152][153][154][155], have shown that macrolides adopt two major conformational families, folded-out and folded-in, referring to the outward and inward folding of the ring fragment 3C-5C ( Figure 5.10). The authors concluded that the vicinal coupling constants 3 J H2H3 and NOE protonproton contacts such as H3-H11 and H4-H11 are good indicators of aglycone fold-ing.…”
Section: Macrolide-ribosome Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results [146][147][148][149][150], and those of other groups [151][152][153][154][155], have shown that macrolides adopt two major conformational families, folded-out and folded-in, referring to the outward and inward folding of the ring fragment 3C-5C ( Figure 5.10). The authors concluded that the vicinal coupling constants 3 J H2H3 and NOE protonproton contacts such as H3-H11 and H4-H11 are good indicators of aglycone fold-ing.…”
Section: Macrolide-ribosome Interactionsmentioning
confidence: 99%
“…Novak et al [146][147][148][149][150] have shown that a systematic approach combining NMR and molecular modelling calculations could be applicable to conformational studies of free and bound macrolides and their interactions with ribosomes. Their results [146][147][148][149][150], and those of other groups [151][152][153][154][155], have shown that macrolides adopt two major conformational families, folded-out and folded-in, referring to the outward and inward folding of the ring fragment 3C-5C ( Figure 5.10).…”
Section: Macrolide-ribosome Interactionsmentioning
confidence: 99%
“…the azithromycin, at least, not in a significant extent. It is more likely that outstanding membrane transfer properties of azithromycin are connected to its ability to form two conformations, referred to as folded-in and folded-out conformations [25,26]. The fraction of each conformation depends on the polarity of its environment and it is possible that azithromycin undergoes conformational change after having been transferred from one phase into another.…”
Section: Figure 4: Ph Dependence Of the Transfer Potentials Of Erythrmentioning
confidence: 99%
“…Conformational studies on macrolides [12][13][14] have shown the existence of two major conformational families: folded-out and folded-in, referring to the outward and inward folding of the macrocycle ring fragment C3-C5. Those studies demonstrated that vicinal coupling constants 3 J H2H3 and NOE proton-proton contacts H4-H11 and H3-H11, respectively, can serve as good indicators of the ring folding.…”
Section: Structural Elucidationmentioning
confidence: 99%
“…The inverse 1 H- 13 C correlation experiment gHMQC was recorded at 125.77 MHz using data matrices of 2K x 256 with 4 scans and processed with a shifted sine bell window function and linear prediction. HMBC spectra were recorded using a transfer delay for the evolution of long range C-H couplings of 60 ms with 256 increments into a matrix of 4Kx2K data points, with a sweep width of 7000Hz in f2 dimension and doi: 10.5599/admet.2.3.47 181 31500 Hz in f1 dimension.…”
Section: Electrochemical Synthesis Ofmentioning
confidence: 99%